A multiscale approach reveals regulatory players of water stress responses in seeds during germination. (24th February 2020) - Saux, Marine; Ponnaiah, Maharajah; Langlade, Nicolas; Zanchetta, Catherine; Balliau, Thierry; El‐Maarouf‐Bouteau, Hayat; Bailly, Christophe
Abstract: Seed germination is regulated by environmental factors, particularly water availability. Water deficits at the time of sowing impair the establishment of crop plants. Transcriptome and proteome profiling was used to document the responses of sunflower ( Helianthus annuus ) seeds to moderate water stress during germination in two hybrids that are nominally classed as drought sensitive and drought tolerant. Differences in the water stress‐dependent accumulation reactive oxygen species and antioxidant enzymes activities were observed between the hybrids. A pathway‐based analysis of the hybrid transcriptomes demonstrated that the water stress‐dependent responses of seed metabolism were similar to those of the plant, with a decreased abundance of transcripts encoding proteins associated with metabolism and cell expansion. Moreover, germination under water stress conditions was associated with increased levels of transcripts encoding heat shock proteins. Exposure of germinating seeds to water stress specifically affected the abundance of a small number of proteins, including heat shock proteins. Taken together, these data not only identify factors that are likely to play a key role in drought tolerance during seed germination, but they also demonstrate the importance of the female parent in the transmission of water stress tolerance. Abstract : Although the mechanisms of water stress response are well described at the whole plant level they remain poorly studied during seed germination, even though this phenological stage is critical for establishment of a novel generation. Here we have compared the molecular mechanisms associated with tolerance to water stress during germination of seeds of two sunflower hybrids. We show that perception of water restriction by germinating seeds involves reactive oxygen species homeostasis and antioxidant mechanisms and that the ability to complete this process is associated with the differential expression of a set of genes among which Heat Shock Proteins are over‐represented.